The Concept of Eloquence in Arabic Literary Theory as Presented by the Eleventh-Century North-African Poet-Critic Ibn Rashiq Al-Qayrawani - Cowell, Dustin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Concept of Eloquence in Arabic Literary Theory as Presented by the Eleventh-Century North-African Poet-Critic Ibn Rashiq Al-Qayrawani